2014
DOI: 10.1007/s10815-014-0350-9
|View full text |Cite
|
Sign up to set email alerts
|

The strategy of group embryo culture based on pronuclear pattern on blastocyst development: a two center analysis

Abstract: Two strategies of group culture gave similar results in terms of blastulation rate but the random grouping of zygotes improves pregnancy and implantation rates in IVF-cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…In animal models, small culture volume as well embryo grouping have been proposed as two different strategies to improve embryo developmental potential [2,4,5,7,8,10,18,19,30] since autocrine and paracrine factors of embryonic origin are likely to mimick in vivo conditions [1,4,5,7,9,13]. In a recent review, Reed and coauthors [7] describe the impact of group versus individual cultures on embryo development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal models, small culture volume as well embryo grouping have been proposed as two different strategies to improve embryo developmental potential [2,4,5,7,8,10,18,19,30] since autocrine and paracrine factors of embryonic origin are likely to mimick in vivo conditions [1,4,5,7,9,13]. In a recent review, Reed and coauthors [7] describe the impact of group versus individual cultures on embryo development.…”
Section: Discussionmentioning
confidence: 99%
“…Studies concerning embryo physiology and metabolism have highlighted the importance of autocrine and paracrine growth factors affecting embryo development in vivo [1][2][3][4][5][6][7][8][9][10]. However, recent data have shown that preimplantation embryos promote their own development in vitro also in absence of paracrine factors secreted by the female reproductive tract [4,6,7,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…For ICSI, denudation of the cumulus oophorus was performed as previously described [2324]. Inseminated or injected oocyte were grouped cultured in microdrops of equilibrated HSA-supplemented Fertilization or Serum Substitute Supplement (SSS, Irvine, CA, USA)-supplemented Cleavage medium (Sage In-Vitro Fertilization, Inc. Trumbull, CT, USA) under oil respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In the study by Ebner et al [5], grouped culture was compared to individual culture with or without possible medium exchange, and a higher blastulation rate was observed in the grouped culture (55.8 versus 40.8 and 45.2 %, respectively, per normally fertilized zygote). An equally low blastocyst formation rate (∼40 %) was observed in the study of Restelli et al [13] where random versus Bdefinite^(based on the zygote type) grouping was compared. The study of RebollarLazaro and Matson [12] showed a significantly higher rate of usable blastocysts when grouped culture was performed until day 3 (51.3 %) compared to single culture to day 5 (46.5 %).…”
Section: Discussionmentioning
confidence: 83%
“…Despite the long history of IVF, the best culture system is yet to be elected and the majority of the labs use different methods to culture their embryos. At present, three major embryo culture systems are used: (i) grouped culture, with three to five human zygotes/embryos cultured together [22,5,12,13], (ii) individual culture, where every embryo is cultured in an individual droplet [22,10,12], and (iii) individual culture with medium exchange between embryo droplets, where although the embryos are cultured individually, the presence of small communicating orifices in the walls allow the passage of medium [5]. Besides the culture system, the choice of the culture medium is also important and may be either: (i) single media, in which the zygote/embryo is cultured from day 0/1 until day 5 or (ii) sequential media, composed of both a cleavage and a blastocyst medium, in which a consecutive medium change is performed on day 3 of embryo development.…”
Section: Introductionmentioning
confidence: 99%